The Effect of Business Location on Sales Result in the Traditional Market - Hanum, Fauziah; Ritonga, Zuriani; Rambe, Bhakti Helvi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
Accuracy in choosing a location is one of the factors that determine the success of a business. Entrepreneurs always have a location close to customers in order to provide primary service to customers so that relationships can be maintained properly. The right business location is expected to meet consumer expectations in order to obtain profit, but if there is an error in choosing a business location automatically the maximum profit will not be obtained by the entrepreneur. The purpose of this research was to determine the effect of choosing a business location on sales. The selection of sales locations is very influential on the sales results of traders. Place/location of business is one element of the marketing mix which is very important for the continuity of a business. This type of research includes field research, namely the new market clothing store and the old market in the Rantauprapat. This research is descriptive, because this study seeks to collect existing facts. This research focuses on efforts to reveal a problem and the situation as it is, which is examined is the technique of interviewing and documentation. While the data analysis was carried out using the data obtained in the form of descriptions, then the data were analyzed using inductive thinking. The results of the research indicate that there is a very strong relationship between the place of business and the profit. The place of business has a positive effect on the profits obtained by the trader.